Increasing Magnetic Blow-Out Force by Using Ferromagnetic Side Plates inside MCB - Kolimas, Ł. (MDPI, 2022)
The paper presents a modern method of computer modeling, concerning the low-voltage extinguishing chambers employed in modular apparatuses. The focus was put on presenting the phenomenon of increasing the blow-out, through the use of ferromagnetic plates, dividing the electric arc inside the electrical apparatus. The use of ferromagnetic material for the production of extinguishing chambers results in the distortion of the magnetic field generated by the electric arc. This creates a magnetic force that draws the arc towards the plate area of the extinguishing chamber. The authors presented a modern tool for the analysis of physical phenomena inside the extinguishing chamber. The presented material makes it possible to examine the influence of changes in the geometry and materials of the mentioned components on the process of switching off the current. The applied approach can be used to analyze physical phenomena in devices, not only for alternating current, but also for direct current. Moreover, the model is scaled to the various parameters of these devices. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.